2019
DOI: 10.1289/ehp3915
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects of Household Solid Fuel Use: Findings from 11 Countries within the Prospective Urban and Rural Epidemiology Study

Abstract: Background:Household air pollution (HAP) from solid fuel use for cooking affects 2.5 billion individuals globally and may contribute substantially to disease burden. However, few prospective studies have assessed the impact of HAP on mortality and cardiorespiratory disease.Objectives:Our goal was to evaluate associations between HAP and mortality, cardiovascular disease (CVD), and respiratory disease in the prospective urban and rural epidemiology (PURE) study.Methods:We studied 91,350 adults 35–70 y of age fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(87 citation statements)
references
References 35 publications
3
82
2
Order By: Relevance
“…Several studies separately evaluated the CVD impacts of solid fuel stove use [42][43][44][45]. In China, solid fuel stove use was associated with a greater risk of CVD mortality (range of hazard ratios (HRs): 1.20-1.29) [44].…”
Section: Air Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies separately evaluated the CVD impacts of solid fuel stove use [42][43][44][45]. In China, solid fuel stove use was associated with a greater risk of CVD mortality (range of hazard ratios (HRs): 1.20-1.29) [44].…”
Section: Air Pollutionmentioning
confidence: 99%
“…In Iran, the use of kerosene stoves was positively associated with CVD mortality (HR: 1.11) in adults, though no association was observed for wood-stove users [46]. Most recently, a multi-country cohort study observed an increased risk of CVD hospitalizations, fatal and nonfatal events, and CVD mortality (range of HRs: 1.04-1.10) among users of solid fuel cookstoves [43]. These studies are supported by studies of subclinical CVD endpoints showing higher levels of inflammatory markers, blood pressure, and arterial stiffness in women using solid fuel stoves and with higher PM 2.5 exposures, with larger associations in older age [42,[47][48][49].…”
Section: Air Pollutionmentioning
confidence: 99%
“…The use of polluting cooking fuels presents a serious global health risk due to household air pollution (HAP) exposure. Elevated levels of fine particulate matter of diameter <2.5 mm (PM 2.5 ) due to HAP (HAP-PM 2.5 ) have been linked to respiratory diseases (child pneumonia [3], COPD [4] and lung cancer [5]), adverse pregnancy outcomes [6,7], cataracts [8], precursors to cardiovascular diseases (CVD), including hypertension [9], and to CVD [10][11][12][13]. Exposure to HAP was the second highest environmental risk factor in the Global Burden of Disease 2017 [14], with an estimated 1.64 million attributable deaths [1,15].…”
Section: Introductionmentioning
confidence: 99%
“…In this cohort of female participants, use of biomass fuel for cooking and heating generated high levels of air pollution that exceed air pollution levels in most urban settings [51] and were 2-8 times higher than the World Health Organization (WHO) health target of 35 μg/m 3 for PM 2.5 [52]. Exposure to air pollutants from biomass stoves have been associated with higher blood pressure in women [53,54] and solid fuel users reported higher incidence and mortality in cardiorespiratory diseases when compared with clean fuel users [3,55]. Although we did not confirm the association of uric acid and/or adenosine to chronic diseases, our pilot work does set the stage for further examination of the underpinning mechanism of HAP exposure and the potential clinical relevance of these discriminatory metabolites.…”
Section: Discussionmentioning
confidence: 99%